The value of play for conflict management: a case study - Blunt, R (South African journal of education, 2009)
This is a case study of a conflict management intervention in two secondary schools in post-apartheid South Africa. The feature of the intervention that we examine is the use of play as an educational strategy. The literature attests that play can facilitate change by allowing learners freedom to change their behaviour and opportunities to explore their new identities. The context of the case revealed that conflicts had become deeply entrenched over time. The literature on conflict management suggests that such situations can change if approached in the right way. In the article we describe the intervention and evaluate it with the help of feedback received from participants and facilitators. In the evaluation we found that the participants were able to overcome prejudices and develop democratic approaches to conflict. The evaluation was repeated several months later, when it was found that the benefits of the workshop had been maintained, with the result that the participants were engaging in healthier relationships. Keywords: communication; conflict management; diversity; elicitive training; games; multicultural; play; problem-solving; role play; secondary schools South African Journal of Education Vol. 29 (1) 2009: pp. 53-6